Manner of Narration in the Prose of Virginia Woolf - Parmonova Nasiba (Zien Journals, 2022)
This article is dedicated to the prose of Virginia Woolf. All of her novels are a kind of journey into the depths of a personality that the reader may or may not accept, but to which he has no right to dictate and impose anything. That's why Woolf argued with realists in her essays. Her compatriot, the writer E.M. Forster, in a lecture dedicated to the writer and read at Cambridge, noted the humor and musicality of her prose, the poetic airy method and the influence of feminism.
Keywords: prose; feminism; Bloomsbury group; the problems of women's emancipation